Grating-incoupled waveguide-enhanced Raman sensor. - Mohamed A Ettabib; Bethany M Bowden; Zhen Liu; Almudena Marti; Glenn M Churchill; James C Gates; Michalis N Zervas; Philip N Bartlett; James S Wilkinson (PLoS ONE, 2023)
We report a waveguide-enhanced Raman spectroscopy (WERS) platform with alignment-tolerant under-chip grating input coupling. The demonstration is based on a 100-nm thick planar (slab) tantalum pentoxide (Ta2O5) waveguide and the use of benzyl alcohol (BnOH) and its deuterated form (d7- BnOH) as reference analytes. The use of grating couplers simplifies the WERS system by providing improved translational alignment tolerance, important for disposable chips, as well as contributing to improved Raman conversion efficiency. The use of non-volatile, non-toxic BnOH and d7-BnOH as chemical analytes results in easily observable shifts in the Raman vibration lines between the two forms, making them good candidates for calibrating Raman systems. The design and fabrication of the waveguide and grating couplers are described, and a discussion of further potential improvements in performance is presented.